A THE EFFECTIVENESS OF IMPLEMENTATION OF PERSONNEL MANAGEMENT INFORMATION SYSTEM IN THE AGRICULTURE DEPARTMENT OF SOUTH SUMATERA PROVINCE - Putri Rizki Efrizal; Dian Maulina (Jurnal Prodi Ilmu Komunikasi, 2022)
The article intends to find out about the effective implementation of the Personnel Management Information System (SIMPEG) at the Department of Agriculture, Food Crops and Horticulture. This writing uses a qualitative descriptive method where this research activity will include an explanation of data input, data collection processes and data output. Basically SIMPEG is a process in processing employee data functionally or procedures and work rules per field in the Food Crops Agriculture Service. And Horticulture which will become information that will be useful for employees both at the district level and on other parties, one of which is the head office. The Personnel Management Information System (SIMPEG) at the Department of Agriculture, Food Crops and Horticulture is formed or made in order to change procedures or manual work rules into a procedure or digital work rules in certain sections while still emphasizing the existing system or integration in both. The Personnel Management Information System (SIMPEG) can also be used as a direction in making decisions made by the manager. Mpin.However, the implementation of the Personnel Management Information System (SIMPEG) at the Department of Food Crops and Horticulture is less effective due to a lack of understanding or guidance regarding the Personnel Management Information System (SIMPEG) provided to employees at the Department of Food Crops and Horticulture.